2020
DOI: 10.1111/add.15040
|View full text |Cite
|
Sign up to set email alerts
|

A latent class analysis of changes in adolescent substance use between 1988 and 2011 in Sweden: associations with sex and psychosomatic problems

Abstract: Aims To characterize changes in patterns of adolescent substance use in Sweden between 1988 and 2011, and to assess whether sex and psychosomatic problems were associated with substance use and whether these associations changed over time. Design Secondary analysis of repeated cross‐sectional survey data. Survey data were collected eight times and analyzed as four cohorts (1988–91, 1995–98, 2002–05 and 2008–11). Setting and participants The sample included all 15–16‐year‐olds in Värmland County, Sweden (n = 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
0
7
0
2
Order By: Relevance
“…However, high-risk substance use patterns [e.g., polysubstance use (PSU)] yield serious negative consequences, including unintentional injury, poorer psychological functioning, more persistent patterns of substance misuse and problems, and fatal and nonfatal overdose (Connor et al, 2014; Peppin et al, 2020; Saunders et al, 2016). Research characterizing the heterogeneity of use patterns has identified between three and five types of young adult substance users: Polysubstance users (PSU), nonusers or infrequent users, and users of specific combinations or levels of use (Bailey et al, 2019; Evans et al, 2020; Evans-Polce et al, 2016; Shi et al, 2020). In the existing PSU literature, the following three latent classes typically emerge: limited-range polysubstance users (LR PSU; using alcohol/tobacco/cannabis); moderate-range PSU (in which amphetamines are added), and extended-range polysubstance users (ER PSU; in which other nonmedical prescription drug use and illicit drug use are added; Connor et al, 2014; Saunders et al, 2016).…”
Section: Age-related Patterns During Young Adulthoodmentioning
confidence: 99%
“…However, high-risk substance use patterns [e.g., polysubstance use (PSU)] yield serious negative consequences, including unintentional injury, poorer psychological functioning, more persistent patterns of substance misuse and problems, and fatal and nonfatal overdose (Connor et al, 2014; Peppin et al, 2020; Saunders et al, 2016). Research characterizing the heterogeneity of use patterns has identified between three and five types of young adult substance users: Polysubstance users (PSU), nonusers or infrequent users, and users of specific combinations or levels of use (Bailey et al, 2019; Evans et al, 2020; Evans-Polce et al, 2016; Shi et al, 2020). In the existing PSU literature, the following three latent classes typically emerge: limited-range polysubstance users (LR PSU; using alcohol/tobacco/cannabis); moderate-range PSU (in which amphetamines are added), and extended-range polysubstance users (ER PSU; in which other nonmedical prescription drug use and illicit drug use are added; Connor et al, 2014; Saunders et al, 2016).…”
Section: Age-related Patterns During Young Adulthoodmentioning
confidence: 99%
“…Despite this, we can examine the classes found across several studies and see that research on problem gambling typically reports a three- [12][13][14] or four-class pattern [15,16] , with increasing severity between classes. Similarly, substance use has been found to t a three-class [17][18][19][20] , or four-class model [21,22] , categorised by severity. Interestingly, Deleuze, Rochat [23] investigated both behavioural and substance addiction and found three theoretical subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…Evans and colleagues [1] found that adolescents who presented more psychosomatic symptoms had higher odds of alcohol and polysubstance use. The authors highlight that throughout the study period this association remained stable, and intervention strategies that address both adolescent substance use and psychosomatic problems may be appropriate.…”
mentioning
confidence: 99%